Getting animated about routine data: co-producing a video and toolkit with young families - Lugg-Widger, Fiona; Segrott, Jeremy; Gee, Peter; Kenkre, Joyce; Robling, Mike (International Journal of Population Data Science, 2018)
Introduction While public engagement activity in healthcare may include a focus on uses of patient data, use of social care/ education data may be relatively overlooked. The public may be less aware about how their social care data may be used. Some concepts such as benefits and risks may also differ. Objectives and Approach Our objective is to co-produce with members of the public a package of materials that researchers may then use to promote public understanding of and engagement in research that uses routine data from health and social care settings. We are running workshops with two groups of young families (teenage mothers, some of whom have received specialist home-visiting support) to explore key concepts and messages about routine data use, including sensitive data such as maltreatment and regulatory child protection interventions. The workshop includes completing a story board for an animated video. This will be co-produced by the same young people. Results Our recent work with young families has shown a preference for visual based methods over text-based approaches to explain routine data linkage. This represents a key opportunity for innovation. We have explored how members of the public understand and make sense of routine data from various settings (health/social care) and its use in research. Working with a professional animator, the co-production of a prototype animation aims to engage members of the public about the nature, benefits and safeguards of using routine public records in health and social care research. The presentation will summarise the method of co-production, review the prototype animation and associated materials for researchers (‘toolkit’). Finally, we will recap key messages identified from the workshops that underpin the animation and other dissemination plans. Conclusion/Implications Our existing understanding of public views (e.g. from consumer panels) may not represent well perspectives from population groups, such as teenage parents. Working with young families who may otherwise rarely engage in such work provides their unique perspectives, adding richness to our understanding of public views on routine data usage.